Screening protocol for freshwater filamentous macroalgae bioremediation of primary municipal wastewater - Indira N. Novak; Marie Magnusson; Rupert J. Craggs; Rebecca J. Lawton (Journal of Applied Phycology, 2024)
A screening protocol was developed and applied to isolate and select cultivars of freshwater filamentous macroalgae for year-round monoculture cultivation and nutrient bioremediation of primary municipal wastewater. The screening protocol is a step-by-step guide to identify robust cultivars which possess key attributes of competitive dominance, high biomass productivity and bioremediation performance under local seasonal and extreme conditions. Forty-four mixed samples of freshwater filamentous macroalgae were collected during summer and winter from a range of local aquatic environments. Eleven isolated cultivars were grown in primary treated municipal wastewater and their biomass productivity and bioremediation performance under local ambient (summer and winter), extreme summer (max. summer) and winter (min. winter) conditions were assessed. Extreme conditions proved to be an important determining factor for cultivar selection as biomass productivity and bioremediation performance significantly declined under min. winter conditions. However, biomass productivity was not directly related to bioremediation performance, as cultivars with low growth rates maintained high nutrient removal rates under min. winter conditions. Top performing cultivars were Klebsormidium sp. (KLEB B) which reduced total ammoniacal-N concentrations by 99.9% to 0.01 mg L -1 (± 0.01 SE), Oedogonium sp. (OEDO D) which reduced nitrate-N concentrations by 90.2% to 0.08 mg L -1 (± 0.7 SE) and Rhizoclonium sp. which reduced phosphate concentrations by 98.7% to 0.02 mg L -1 (± 0.01 SE). Based on overall biomass productivity and bioremediation performance across seasonal and extreme conditions Klebsormidium sp. (KLEB B) , Stigeoclonium sp. (STIG A) and Ulothrix sp. were identified as top performing cultivars suitable for the nutrient bioremediation of primary municipal wastewater.